1996
DOI: 10.1111/j.1469-8137.1996.tb01868.x
|View full text |Cite
|
Sign up to set email alerts
|

Catechin, proanthocyanidin and lignin contents of loblolly pine (Pinus taeda) needles after chronic exposure to ozone

Abstract: SUMMARYConcentrations of soluble and bound phenolic cotnpounds were measured in needles of 3-yr-old loblolly pme {Pinus taeda L.) trees exposed from May to November 1993 to a range of ozone (O3) concentrations in open-top fidd chambers. The treatments were charcoal-filtered air (CF). non-filtered air (NF), and NF air with O, added at 1-5 times (NF 1-5) and 2-0 times (NF 2-0) the ambient O, concentration for 12 h daily. Average daily (0800-2000 hours) O3 concentrations in the CF.NF, NF ISandNF 2 0 treatments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 29 publications
1
51
1
Order By: Relevance
“…According to the present study and most earlier studies, O 3 did not have signiÂźcant eects on needle total phenolic concentrations (Jordan et al 1991;Kainulainen et al 1994Kainulainen et al , 1995aBooker et al 1996). However, higher concentrations of total phenolics (Tingey et al 1976;Kainulainen et al 1994) and some individual phenolic compounds (Kicinski et al 1988;Rosemann et al 1991) were found in conifers exposed to higher O 3 concentrations than used in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…According to the present study and most earlier studies, O 3 did not have signiÂźcant eects on needle total phenolic concentrations (Jordan et al 1991;Kainulainen et al 1994Kainulainen et al , 1995aBooker et al 1996). However, higher concentrations of total phenolics (Tingey et al 1976;Kainulainen et al 1994) and some individual phenolic compounds (Kicinski et al 1988;Rosemann et al 1991) were found in conifers exposed to higher O 3 concentrations than used in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…Heavy metal induced changes in the phenolic compounds may further affect their functions in plant cells. Phenolic compounds, including tannins, are often involved in responses to different kinds of abiotic and biotic stresses (Rivero 2001;Booker et al 1996;Dixon and Paiva 1995;Yamasaki et al 1995). It is reported that in plant systems, phenolics can act as antioxidants by donating electrons to guaiacol-type peroxidases (GuPXs) for the detoxification of H 2 O 2 produced under stress conditions including heavy metal stress (Sakihama et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that chronic as well as acute O 3 exposures impact gene regulation (Ernst 2013;Renaut et al 2009) even though acute episodes could provoke more important changes than chronic ones (Ainsworth et al 2012;Ernst 2013). Furthermore, proteomic analysis confirms the downregulation of a large number of proteins involved in the Calvin-Benson cycle in poplar leaves exposed to chronic O 3 , as well as proteins involved in chloroplastic electron transport (Bohler et al 2007). O 3 also decreases chloroplast size and cell starch content ).…”
Section: Carbon Assimilation and Leaf Senescencementioning
confidence: 94%